A NARRATIVE REVIEW ON ADVANCEMENTS AND CHALLENGES IN PALLIATIVE CARE FOR ELDERLY PATIENTS WITH HIP FRACTURES. - Gautam Kumar, (Student's Journal of Health Research Africa, 2024)
Hip fractures in the elderly are a major public health issue, with a rising incidence due to the aging global population. These fractures not only cause significant physical disability but also lead to psychological and social challenges, with a high associated mortality rate. Surgical decision-making in hip fracture repair is complex, requiring careful consideration of the patient's overall health, comorbidities, and life expectancy. This review aims to explore the multifaceted approach to managing hip fractures in the elderly, focusing on surgical decision-making, the role of palliative care, and the balance between curative and palliative treatment strategies. The review discusses the epidemiology and risk factors of hip fractures, highlighting the need for preventive strategies. It delves into the surgical decision-making process, examining the criteria for intervention and the outcomes of different surgical approaches. The role of palliative care is emphasized, focusing on pain management, quality of life, and support for families and caregivers. The review underscores the importance of a multidisciplinary approach in managing these patients, involving both surgical intervention and comprehensive palliative care. The findings suggest a need for evolving clinical policies that integrate palliative care principles into the management of hip fractures in the elderly. Future implications include developing standardized protocols for surgical decision-making and enhancing palliative care services to improve patient outcomes.